1987
DOI: 10.1159/000205876
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload and Iron Chelation Therapy in Thalassaemia and Sickle Cell Haemoglobinopathies

Abstract: This paper reviews the factors governing the rate of iron loading and iron toxicity in the thalassaemia syndromes and sickle cell disease. It outlines the main determinants of iron mobilization by the iron-chelating drug, desferrioxamine, together with the effects of this drug in clinical practice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…When patients with iron overload are admitted to hospital with noninfectious complaints, we often give deferoxamine 3 grams in 500 mL normal saline intravenously over 24 hours, repeating continuously during their stay. Giving Vitamin C 250 mg orally daily while the patient is on deferoxamine increases iron excretion [107, 108]. Ongoing cohort studies should help define the natural history of iron overload in sickle cell patients [109111].…”
Section: Gastrointestinal/hepatobiliary Complicationsmentioning
confidence: 99%
“…When patients with iron overload are admitted to hospital with noninfectious complaints, we often give deferoxamine 3 grams in 500 mL normal saline intravenously over 24 hours, repeating continuously during their stay. Giving Vitamin C 250 mg orally daily while the patient is on deferoxamine increases iron excretion [107, 108]. Ongoing cohort studies should help define the natural history of iron overload in sickle cell patients [109111].…”
Section: Gastrointestinal/hepatobiliary Complicationsmentioning
confidence: 99%
“…In another study, marked iron overload was found in the liver, spleen, and kidney with complete absence of iron in the bone marrow despite elevated ferritin. Pippard et al [54] have hypothesized that SCD patients have a significantly different clinical course compared with β-thalassemia patients because their iron stores remain locked in a non-toxic form in RE system macrophages longer than in β-thalassemia patients. In a 1994 review, the authors suggested that SCD patients may be at significantly less risk of iron overload because of the pathologic iron deposition induced by inflammation in SCD [55].…”
Section: Basic Iron Metabolism In Scdmentioning
confidence: 99%
“…33 Iron chelation therapy with intravenous or subcutaneous deferoxamine is recommended, as untreated, this condition can progress to hepatic fibrosis and cirrhosis. 44 …”
Section: Sickle Cell Intra-hepatic Cholestasismentioning
confidence: 99%